PERAN PEMBERDAYAAN MASYARAKAT DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Darda Abdullah Sjam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is a fundamental aspect that should be instilled from an early age, particularly at the elementary school level. One of the essential character values to be developed is the spirit of mutual cooperation and social care. These values can be cultivated through various approaches, one of which is community empowerment. This study aims to examine the role of community empowerment in fostering the values of mutual cooperation and social care through character education in elementary schools. The research employs a qualitative approach using a literature study method by analyzing relevant books and scholarly journal articles. The findings indicate that community empowerment plays a significant role in strengthening the values of mutual cooperation and social care among students, teachers, and the surrounding community. Active community involvement in character education activities enhances students’ social awareness, cooperative skills, and empathy. Furthermore, community empowerment contributes to improving the quality of character education implementation in a contextual and sustainable manner at the elementary school level. Keywords: character education, community empowerment, mutual cooperation, social care, elementary school. ABSTRAK Pendidikan karakter merupakan aspek fundamental yang perlu ditanamkan sejak usia dini, khususnya pada jenjang sekolah dasar. Salah satu nilai karakter yang penting untuk dikembangkan adalah jiwa gotong royong dan kepedulian sosial. Penanaman nilai tersebut dapat dilakukan melalui berbagai pendekatan, salah satunya melalui pemberdayaan masyarakat. Penelitian ini bertujuan untuk mengkaji peran pemberdayaan masyarakat dalam menumbuhkan nilai gotong royong dan kepedulian sosial melalui pendidikan karakter di sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, melalui analisis terhadap berbagai buku dan artikel jurnal ilmiah yang relevan. Hasil kajian menunjukkan bahwa pemberdayaan masyarakat berperan signifikan dalam menumbuhkan nilai gotong royong dan kepedulian sosial pada peserta didik, guru, serta masyarakat. Keterlibatan aktif masyarakat dalam kegiatan pendidikan karakter mampu meningkatkan kesadaran sosial, keterampilan bekerja sama, serta empati peserta didik. Selain itu, pemberdayaan masyarakat juga berkontribusi dalam meningkatkan kualitas implementasi pendidikan karakter secara kontekstual dan berkelanjutan di sekolah dasar. Kata kunci: pendidikan karakter, pemberdayaan masyarakat, gotong royong, kepedulian sosial, sekolah dasar.